2020
DOI: 10.1002/gps.5445
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mental and physical multimorbidity on healthcare utilization and health spending in China: A nationwide longitudinal population‐based study

Abstract: Background In China, little evidence exists on the effect of mental and physical multimorbidity on individuals and the health system. This study aims to examine the prevalence of mental–physical multimorbidity and its impact on health service utilization and health expenditures. Methods We conducted a panel study using two waves of data (in 2011 and 2015) from the China Health and Retirement Longitudinal Study, including 10,181 participants aged 45 years and older. Generalized linear regression models were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…The higher treatment cost and financial burden for individuals with multimorbidity are in line with earlier published studies. 6 13 37 Chen et al 13 found that the expenditure on patients with multiple chronic diseases was over three times higher than those with a single disease. This positive relationship between the number of NCDs and OOPE was also consistent with earlier studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The higher treatment cost and financial burden for individuals with multimorbidity are in line with earlier published studies. 6 13 37 Chen et al 13 found that the expenditure on patients with multiple chronic diseases was over three times higher than those with a single disease. This positive relationship between the number of NCDs and OOPE was also consistent with earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…As multimorbidity is costly to individuals and the health systems, there is a need for concerted efforts and other LMICs with ageing populations to reduce the treatment burden among patients with multimorbidity and its impact on financial risk protection. 6 Prevention strategies for NCDs should adopt approaches that take into account multimorbidity in healthcare management, rather than single-disease approaches, particularly in funds allocation and in designing policies on financial protection. 7 Furthermore, preventing multimorbidity and developing more sustainable models of care is a key priority.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In China, people suffering from multimorbidity are inseparable from the level of health service use and the patient's own financial affordability (36). People with multiple chronic diseases must have richer information and flexibility in order to better manage personal health, otherwise they may be faced with more complicated situation (37).…”
Section: Differential Health Effects Of Monopathy and Multimorbiditymentioning
confidence: 99%